A correction method of color projection fringes in 3D contour measurement - 宋丽梅 李宗艳 陈昌曼 习江涛 郭庆华 李晓捷 (Optoelectronics letters, 2015)
In the three-dimensional（3D） contour measurement,the phase shift profilometry（PSP） method is the most widely used one.However,the measurement speed of PSP is very low because of the multiple projections.In order to improve the measurement speed,color grating stripes are used for measurement in this paper.During the measurement,only one color sinusoidal fringe is projected on the measured object.Therefore,the measurement speed is greatly improved.Since there is coupling or interference phenomenon between the adjacent color grating stripes,a color correction method is used to improve the measurement results.A method for correcting nonlinear error of measurement system is proposed in this paper,and the sinusoidal property of acquired image after correction is better than that before correction.Experimental results show that with these correction methods,the measurement errors can be reduced.Therefore,it can support a good foundation for the high-precision 3D reconstruction.